2011
DOI: 10.3389/fnhum.2011.00094
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing Art: The Influence of Expertise and Painting Abstraction Level

Abstract: How does expertise influence the perception of representational and abstract paintings? We asked 20 experts on art history and 20 laypersons to explore and evaluate a series of paintings ranging in style from representational to abstract in five categories. We compared subjective esthetic judgments and emotional evaluations, gaze patterns, and electrodermal reactivity between the two groups of participants. The level of abstraction affected esthetic judgments and emotional valence ratings of the laypersons but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
153
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(181 citation statements)
references
References 33 publications
24
153
2
2
Order By: Relevance
“…The observation that GSR responses were overall higher in controls rather than dancers. This is congruent with previous reported differences between experts and laypersons in other art domains (painting), where novel stimuli typically elicit greater physiological arousal responses than familiar responses (Pihko et al, 2011). This observation does, however, raise interesting questions for future studies in terms of how the effects of novelty/familiarity of stimuli interact with the sensitivity of the observer to affective dimensions.…”
Section: Discussionsupporting
confidence: 89%
“…The observation that GSR responses were overall higher in controls rather than dancers. This is congruent with previous reported differences between experts and laypersons in other art domains (painting), where novel stimuli typically elicit greater physiological arousal responses than familiar responses (Pihko et al, 2011). This observation does, however, raise interesting questions for future studies in terms of how the effects of novelty/familiarity of stimuli interact with the sensitivity of the observer to affective dimensions.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have suggested that expertise in a particular area would promote an expert cognitive strategy in sampling and processing visual information, such as modifying gaze distribution in viewing paintings, watching sports videos and interpreting medical images (e.g., Kundel et al, 2008;Pihko et al, 2011;Crespi et al, 2012;Wood et al, 2014). In this study, we extended this expertise-or experiencedmodified viewing behaviour to the processing of non-conspecific faces by systematically comparing dog-owners' and non-dog-owners' behavioral performance and gaze distribution in judging face approachability.…”
Section: Discussionmentioning
confidence: 99%
“…Such expertise-modulated gaze pattern differences have been observed between expert and novice observers when they look at pictures or art pieces (Zangemeister, Sherman, & Stark, 1995;Vogt & Magnussen, 2007;Humphrey & Underwood, 2009;Pihko et al, 2011), watch sports videos (Crespi, Robino, Silva, & de'Sperati, 2012), read music (Waters, Underwood, & Findlay, 1997), interpret medical images (Nodine, Kundel, Lauver, & Toto, 1996;Donovan & Manning, 2007;Kundel, Nodine, Krupinski, & Mello-Thomas, 2008;Matsumoto et al, 2011;Wood, Batt, Appelboam, Harris, & Wilson, 2014), drive (Underwood, 1998;Nabatilan, Aghazadeh, Nimbarte, Harvey, & Chowdhury, 2012), or play chess (Reingold, Charness, Pomplun, & Stampe, 2001). For instance, in comparison with laypersons, experienced radiologists tend to adopt a more global gaze strategy to 5 examine mammography images in detecting breast cancer (Kundel et al, 2008), arttrained viewers often scan a larger surface of representational paintings and give higher aesthetic rating when evaluating abstract paintings (Pihko et al, 2011), and the experienced drivers fixate more on the front and centre view, and make fewer driving errors when facing visual distraction (Nabatilan et al, 2012). Based on these earlier studies, it is reasonable to assume that for a given task, the pet owners are likely to adopt an experienced-based viewing behaviour to extract informative facial information from familiar non-conspecific faces.…”
Section: Introductionmentioning
confidence: 97%
“…Several works that deal with emotional analysis of images and artworks reports that using the dimensional approach has as advantages the disambiguation of the emotional states and the consistency with the way the brain processes emotion Hanjalic [2006]; Leder et al [2012Leder et al [ , 2014; Lu et al [2012]; Pihko et al [2011]. Nicolaou et al [2011] points out that the automatic emotion recognition models "are deemed unrealistic as they are unable to capture the non-basic and subtle affective states exhibited by humans in everyday interactions".…”
Section: Emotion Recognition: How Can Emotions Be Measured?mentioning
confidence: 99%
“…Analysing eye movements and fixations has been used as an important tool to understand the human perception of an artwork and the features that are closely related to a specific emotion Pihko et al [2011]. Moreover, emotional stimuli were shown to attract attention.…”
Section: Related Workmentioning
confidence: 99%